Vicarious victimization in prison: examining the effects of witnessing victimization while incarcerated on offender reentry - Daquin, Jane C. (Criminal justice and behavior, 2016)
Prison victimization research has mainly focused on direct experiences of victimization rather than on the vicarious victimization experiences of prisoners, despite the possibility of inmates being exposed to high levels of victimization. Using the Prison Experience and Reentry Study, a longitudinal study of 1,613 males residing in Ohio halfway houses, the study examined the extent of witnessing victimization in prison and its effects on individual post-release outcomes. The findings show that a large proportion of offenders witness victimization and that parolees who witnessed victimization faced greater odds of experiencing at least one negative criminal justice outcome, including a parole violation and an arrest. These findings suggest that it is not only direct victimization that plays a role in post-release adjustment.